IMPLEMENTASI METODE PEMBELAJARAN SIDO NEMBANG BERBASIS KEARIFAN LOKAL DALAM MUATAN IPS DI SEKOLAH DASAR - Indah Wardatussa’idah; Taofik; Sarkadi; Dina Santika; Nabila Chairunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Local wisdom can be interpreted as a system in the order of social, political, cultural, economic and environmental life that lives in local communities based on clear reasoning, good manners and containing positive things. In education, methods, strategies, techniques have an important role and position in achieving educational goals because methods are tools for conveying learning that has been studied in the curriculum and can be tools to facilitate the delivery of material to students. Learning methods, playing and singing is a method in the learning process that is fun for children so that they are more enthusiastic, enthusiastic about learning and don't get bored quickly when learning. This activity is very closely related to children and has a close relationship with children's world. The aim of this research is to make it easier for social studies teachers in elementary schools when implementing learning methods adapted to social studies material in class. By implementing the Sido Nembang learning method, it is hoped that students will be able to learn, play and sing well. This research was conducted in elementary schools in the DKI Jakarta area for one year. By using qualitative-based research methods. The final result is that researchers want to see how the implementation of the Sido Nembang learning method based on local wisdom is integrated with material content and sub-themes in social studies subjects in elementary schools.   Keywords: learning methods, local wisdom, social sciences in elementary schools